Political training in and from the school. contributions to build the relationship children – school – politics - Avellaneda Avellaneda, Yenny Tatiana (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article provides, from a critical look, conceptual, theoretical, and methodological elements of reflection on the school–children–politics relationship. Based on those elements the discussion of the meaning of politics in the school context is set out. As a basis for this, the research experience worked out with school communities in Ricaurte,Boyaca was taken into account. In two of these communities the pedagogical innovation proposal, ‘Political Training in and from the School’, focused on promoting action and word as enablers of political training processes in children, was designed and developed. This paper closes with the systematization of the experience, in which some elements of analysis are presented on two emerging categories, namely: empowerment through language, and positioning by means of a transformative creative action.